2003
DOI: 10.1016/s0896-6273(03)00569-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathogenic Forms of Huntingtin and Androgen Receptor Inhibit Fast Axonal Transport

Abstract: Huntington's and Kennedy's disease are autosomal dominant neurodegenerative diseases caused by pathogenic expansion of polyglutamine tracts. Expansion of glutamine repeats must in some way confer a gain of pathological function that disrupts an essential cellular process and leads to loss of affected neurons. Association of huntingtin with vesicular structures raised the possibility that axonal transport might be altered. Here we show that polypeptides containing expanded polyglutamine tracts, but not normal N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
206
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(214 citation statements)
references
References 57 publications
5
206
1
2
Order By: Relevance
“…Consistent with our hypothesis that Htt-Q128 expression causes neurodegeneration secondary to impairment of axonal transport, recent studies have found that neurodegeneration is a primary consequence of axonal transport defects in non-polyQ diseases as well, including Alzheimer's disease (26)(27)(28). During review of our manuscript, two reports have been published that document similar axonal transport defects in HD models (29,30). Determining the precise mechanisms by which Htt aggregates physically attach to the axonal cytoskeleton will likely provide important insights into the mechanisms of axonal transport blockage in HD.…”
Section: Resultssupporting
confidence: 87%
“…Consistent with our hypothesis that Htt-Q128 expression causes neurodegeneration secondary to impairment of axonal transport, recent studies have found that neurodegeneration is a primary consequence of axonal transport defects in non-polyQ diseases as well, including Alzheimer's disease (26)(27)(28). During review of our manuscript, two reports have been published that document similar axonal transport defects in HD models (29,30). Determining the precise mechanisms by which Htt aggregates physically attach to the axonal cytoskeleton will likely provide important insights into the mechanisms of axonal transport blockage in HD.…”
Section: Resultssupporting
confidence: 87%
“…For example, point mutations affecting functional domains in kinesin or dynein motors can produce late-onset dying-back neuropathies in sensory or motor neurons (20,21). Furthermore, dysregulation of FAT has been proposed as a pathological mechanism in several neurological disorders including AD (22, 23), Kennedy's disease (24,25), Huntington's disease (25), and Parkinson's disease (26). These findings highlight the importance of FAT for neuronal survival.…”
mentioning
confidence: 99%
“…Polyglutamine expansion in mutant Htt causes Huntington's disease, a neurodegenerative disorder that primarily affects striatal neurons. Mutant Htt disrupts axonal transport in squid axoplasm (7), Drosophila (8), and mammals (9,10), suggesting a role for the protein in vesicle transport. Htt interacts with various proteins implicated in trafficking (6,11), including Htt-associated protein-1 (HAP1), which in turn interacts with both dynactin and kinesin (12)(13)(14).…”
mentioning
confidence: 99%